Adiponectin as serum biomarker of insulin resistance in patients with polycystic ovarian syndrome. (June 2015) - Niafar, Mitra; Nader, Nader D.
Abstract Objective: To examine the role of adiponectin as a biomarker of insulin resistance in polycystic ovary syndrome (PCOS). Background: PCOS is associated with metabolic syndrome, which correlates to increased cardiovascular risk in these patients. Adiponectin is decreased in obese individuals. Methods: Ninety women with PCOS (45 with and 45 without metabolic syndrome) were enrolled in this study. Anthropometric variables, serum concentrations of fasting glucose, insulin, triglycerides, lipoproteins, cholesterol, testosterone and adiponectin were measured in all patients. Insulin sensitivity was examined in all patients. Numerical values were analyzed by t-tests and categorical data were analyzed by Chi-square test. Multiple regression analyses were performed to detect the factors that contributed to insulin resistance. Results: Metabolic syndrome predicted insulin resistance in PCOS patients. Serum adiponectin levels were suppressed in insulin resistant compared to insulin sensitive patients (10.7 ± 4.3 µg/mL, p < 0.001). Multiple linear regression analysis revealed for every 1 µg increase in adiponectin, insulin sensitivity index increases by 0.1 (p = 0.016). Serum testosterone failed to correlate with insulin sensitivity. Conclusion: Serum adiponectin levels were suppressed in patients with both metabolic syndrome and insulin resistance. This protein could be used as a biomarker to distinguish the patients at a higher risk of diabetes and cardiovascular morbidity.